2017
DOI: 10.1039/c6ra26087j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic damping and perpendicular magnetic anisotropy in Pd-buffered [Co/Ni]5 and [Ni/Co]5 multilayers

Abstract: The magnetic damping α0 increases continuously with underlayer thickness, showing no correlation with PMA strength but a similar variation behavior to 1/Ms. Such α0 increase is ascribed to the formation of more disordered spins at NM/FM interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The Tb 25 Co 75 alloy layer is Tb-rich at room temperature because the magnetization compensation composition of Tb content is known to be ∼22%. The static magnetic properties were measured by a vibrating sample magnetometer (VSM), a physical property measurement system, and a polar magneto-optical Kerr effect (MOKE) system, whereas the dynamic magnetic properties were determined by means of a time-resolved MOKE (TR-MOKE) technique. ,, Both static MOKE and dynamic TR-MOKE measurements were achieved by using a pulsed Ti:sapphire laser with a central wavelength of 800 nm, a pulse duration of 150 fs, and a repetition rate of 1000 Hz. The Kerr signal was recorded according to the Kerr rotation variation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tb 25 Co 75 alloy layer is Tb-rich at room temperature because the magnetization compensation composition of Tb content is known to be ∼22%. The static magnetic properties were measured by a vibrating sample magnetometer (VSM), a physical property measurement system, and a polar magneto-optical Kerr effect (MOKE) system, whereas the dynamic magnetic properties were determined by means of a time-resolved MOKE (TR-MOKE) technique. ,, Both static MOKE and dynamic TR-MOKE measurements were achieved by using a pulsed Ti:sapphire laser with a central wavelength of 800 nm, a pulse duration of 150 fs, and a repetition rate of 1000 Hz. The Kerr signal was recorded according to the Kerr rotation variation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is very essential to study the magnetic dynamics of ferromagnetic films for deeply understanding the fast switching mechanism and manipulating the control parameters of magnetic damping and magnetization precession. However, most of the magnetic dynamics studies are restricted to the individual magnetic thin films. Relevant work on the exchange-coupled composite system is very rare and limited to the directly contacted case with a fixed coupling strength. For instance, Barman et al reported a strong dependence of the precession frequency on the NiFe thickness in FePt/NiFe exchange spring bilayers . The damping constant of GdFeCo/TbFe perpendicular exchange-coupled bilayers was found to increase significantly with the TbFe layer thickness .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their excellent thermal stability and potential applications in ultra-high-density devices, they have garnered strong research interests. [1][2][3][4][5] PMA is a notable behavior that causes the magnetic moment of a magnetic material to be aligned perpendicular to the lm plane, whereas the shape of the thin lm usually makes the magnetic moment parallel to the lm plane. Currently, PMA materials are widely applied in memory and logic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated data is plotted in Fig. 4(b) and fit by the red curves using the widely applied exponential relation  (Hext) = 1exp(−Hext/H0) + 0, where 1 is the coefficient, H0 is a constant, and 0 is the effective damping [33]. The effective damping in 3Py/3Pt and 3Ta/3CoFeB samples were found to be 0.024 and 0.008, respectively.…”
Section: B Dynamic Measurement and Simulationmentioning
confidence: 99%